#TITLE_ALTERNATIVE# - INDRA WIJAYASARI (NIM 25095065), SRI
One of the problems that must be solved for shallow water region is the information about water surface elevation or flow velocity or tidal current which is caused by tidal influence. These information, such as water surface elevation and flow velocity can influence the other problems. To get these information we must observe in the field or we can predict with a model. This thesis discuss about the implementation of finite element method Taylor Galerkin to simulate the distribution of current in shallow water region. This simulation is based on two dimensional depth averaged model which is solved by FEM, with the linier triangle element. The formulation of FEM is built based of the formulation of Two Step Taylor Galerkin Scheme which is first develop by Donea. The solution of global matrix is used a simple iteration which is called Mass Lumping Technique. This model is apllied to some cases, for example straight channel, channel which have different depth, channel with a basin, channel with a obstacle, junction channel and also cases that have complex domain and bathimetry.